The European Union's 'potential We' between acceptance and contestation: assessing the positioning of six eastern partnership countries* - Vieira, Alena (2021)
The present contribution analyses the European neighbourhood policy and the Eastern Partnership (EaP), which celebrated its tenth anniversary in 2019, from the perspective of social identity theory. It is argued that the evolution of both the European neighbourhood policy and the EaP corresponds to the emergence of a distinct EU identity: its 'potential we', which has been defying the Russian 'significant we' extended to the EaP states. Drawing on the framing analysis of strategic documents and statements, which identifies eight distinct themes, the contribution ascertains three different patterns of EaP states' interaction with the EU: Georgia, Moldova and Ukraine accepting the 'EU's potential we', Armenia holding to the potential we, and Azerbaijan, as well as Belarus, contesting the potential we.